Genome editing of pseudorabies virus in the CRISPR/Cas9 era: a mini-review - Wang, Hai-Ming; Qiao, Yang-Yang; Cai, Bing-Yan; Tan, Ju; Na, Lei; Wang, Yu; Lu, Hui; Tang, Yan-Dong (Frontiers in Veterinary Science, 2023)
Pseudorabies virus (PRV) is an important swine virus that has a significant impact on the global swine industry. PRV is a member of the herpesvirus family, specifically the alphaherpesvirus subfamily, and has been extensively utilized as a prototype herpesvirus. Notably, recent studies have reported that PRV sporadically spills over into humans. The PRV genome is approximately 150 kb in size and is difficult to manipulate at the genomic level. The development of clustered regularly interspaced short palindromic repeat-associated protein (CRISPR/Cas9) technology has revolutionized PRV genome editing. CRISPR/Cas9 has been widely used in the construction of reporter viruses, knock-out/knock-in of genes of interest, single virus tracking and antiviral strategies. Most importantly, for vaccine development, virulence gene knockout PRV vaccine candidates can be obtained within two weeks using CRISPR/Cas9. In this mini-review, we provide a concise overview of the application of CRISPR/Cas9 in PRV research and mainly share our experience with methods for efficiently editing the PRV genome. Through this review, we hope to give researchers better insight into the genome editing of pseudorabies virus.